2000
DOI: 10.1111/j.1540-8159.2000.tb06774.x
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking Effect of Propafenone on the Concealed Form of the Brugada Phenomenon

Abstract: A case report of a patient with frequent ventricular premature beats but with an otherwise normal ECG and no structural heart disease. Propafenone in therapeutical doses unmasked the ECG picture of the Brugada phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 9 publications
1
15
0
1
Order By: Relevance
“…1 More prominent ST-segment elevation in the right precordial leads has been observed immediately before or after episodes of aborted sudden cardiac death in some patients, 2,3 but asymptomatic patients with Bru-ECG have been described. [4][5][6] Brugada et al also reported that the incidence of arrhythmic events is similar in symptomatic and asymptomatic patients with Bru-ECG. 7 These reports suggest that all patients with characteristic Bru-ECG are at risk for sudden cardiac death, but the variety of arrhythmic events associated with the Bru-ECG and the relationship between the occurrence of arrhythmic events and STsegment elevation is unknown.…”
mentioning
confidence: 99%
“…1 More prominent ST-segment elevation in the right precordial leads has been observed immediately before or after episodes of aborted sudden cardiac death in some patients, 2,3 but asymptomatic patients with Bru-ECG have been described. [4][5][6] Brugada et al also reported that the incidence of arrhythmic events is similar in symptomatic and asymptomatic patients with Bru-ECG. 7 These reports suggest that all patients with characteristic Bru-ECG are at risk for sudden cardiac death, but the variety of arrhythmic events associated with the Bru-ECG and the relationship between the occurrence of arrhythmic events and STsegment elevation is unknown.…”
mentioning
confidence: 99%
“…13 Induction of VF during the drug challenge test or after the administration of Na + -channel blockers in patients with paroxysmal atrial fibrillation with typical ST-segment elevation has been described. 3,14,15 However, we carefully administered pilsicainide with continuous ECG monitoring and immediately discontinued administration when marked ST-segment elevation, excessive QRS prolongation or ventricular arrhythmias were observed. We completed the drug challenge test safely without any severe adverse events.…”
Section: Na + -Channel-blocker Challenge Test Using Pilsicainidementioning
confidence: 99%
“…24, 25 In Japan, pilsicainide, which is a pure Na + -channel blocker and a class Ic drug in the Vaughan Williams classification, 26 is usually administrated intravenously at 0.1 mg · kg -1 · min -1 over 10 min (total, 1 mg/kg). Other class I anti-arrhythmic agents have ion-channel-blocking effects not only on the Na + channels but also on K + channels, including Ito, which results in a spike-and-dome morphology of the epicardial action potential.…”
Section: Na + -Channel-blocker Challenge Testmentioning
confidence: 99%